The Sky is the Limit; I am Going There”: Experiences of Hope Among Young Women Receiving a Conditional Cash Transfer in Rural South Africa - Kaitlyn Atkins; Catherine MacPhail; Suzanne Maman; Nomhle Khoza; Rhian Twine; F Xavier Gomez-Olive; Audrey Pettifor; Kathleen Kahn (My University, 2021)
Young women in South Africa face elevated risk of HIV infection compared to male peers. Cash transfers may mitigate their risk for HIV; however, there is limited understanding of mechanisms of impact. We explored hope as one potential mechanism. Longitudinal qualitative analysis was used to explore how cash transfer recipients in the HPTN 068 study conceptualised hope and how the intervention influenced their hope over time. We found the intervention increased confidence, alleviated financial stressors and instilled in young women the belief that a better life, defined as being educated, independent and supportive to family, was attainable. Findings support hope as a critical outcome of cash transfer and other economic strengthening interventions.
Keywords: HIV prevention; South Africa; hope; poverty; young women.